The Dales of Arcady - Ratcliffe, Dorothy Una, 1891-1967 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Dales of Arcady" by Dorothy Una Ratcliffe is a collection of lyrical poetry written in the early 20th century. This book explores the enchanting rural landscapes of Yorkshire, specifically the dales, moors, and rivers, encapsulating the natural beauty and tranquility of these regions. The work vividly evokes the themes of nature, romance, and nostalgia, presenting a rich tapestry of the author's love for the English countryside. Throughout the poems, Ratcliffe invites readers to experience the diverse experiences and sights of the dales. The writing captures the essence of each season and the joys of rural life, portraying characters that range from the musing poet to divine beings like Pan who engage with the mortal realm. The collection includes evocative imagery of blooming flowers, singing birds, and the gentle embrace of nature, while also addressing deeper themes such as love, loss, and the passage of time, celebrating the enduring beauty of the natural world amidst human feelings and experiences. Each poem serves as an embrace of the landscapes Ratcliffe holds dear, providing a meditative retreat into the pastoral life. (This is an automatically generated summary.)
Release date is 2011-08-14
Produced by Al Haines
Keywords: Yorkshire (England) -- Poetry